Smartphone-Based High-Throughput Fluorimetric Assay for Histidine Quantification in Human Urine Using 96-Well Plates - Dimitrios Baltzis; George Z. Tsogas; Constantinos K. Zacharis; Paraskevas D. Tzanavaras (Molecules, 2023)
A high-throughput fluorimetric assay for histidine was developed, using a 96-well plates platform. The analyte reacts selectively with o-phthalaldehyde under mild alkaline conditions to form a stable derivative. Instrumental-free detection was carried out using a smartphone after illumination under UV light (365 nm). The method was proved to be linear up to 100 μM histidine, with an LLOQ (lower limit of quantification) of 10 μM. The assay was only prone to interference from glutathione and histamine that exist in the urine samples at levels that are orders of magnitude lower compared to histidine. Human urine samples were analyzed following minimum treatment and were found to contain histidine in the range of 280 to 1540 μM. The results were in good agreement with an HPLC corroborative method.